GOVERNMENT AND THE DAGESTAN SOCIETY IN THE PERIOD OF THE WORLD WAR I: DAILY EXPERIENCE - Dalgat, El'mira Murtuzalievna; Abdulaeva, Madina Izamutdinovna; Aagan, Burkitbaj Gelmanovic (History, Archeology and Ethnography of the Caucasus, 2020)
The article examines poorly studied issues of relations and interactions between the regional authorities and the Dagestan society during the events of the World War I, which impacted greatly the everyday lives of the inhabitants of the region.The relevance of the topic is quite evident in the light of modern events, when the crisis of power and society in a number of countries led to the so-called “color revolutions”. The historical lessons of social cataclysms give us an opportunity to model and anticipate certain events. Interdisciplinary approach to studying social, political, economic aspects of world-view of various strata of the population and their psychological perception of war and relations with authorities allow us to show the historical reality. The rejection of the ideology, which considered the First World War exclusively as a forerunner of the revolution, the introduction of memoirs, works of foreign researchers, the identification and display of the personal factor put more emphasis in favor of social anthropology.During the war, the daily life of the Dagestan region, as one of the remote areas of the Czarist Russia, bore common imperial features, while at the same time had its own peculiarities. However, as factual material reveals, the events, which affected the front-line territories, took place in Dagestan only in 1916. The analysis of the ratio of the characteristic aspects of the regional and all-Russian current situation has made it possible to identify other distinctive characteristics of the daily life of the Dagestan society. By the end of 1916, the economic and political crisis also came to the Dagestan region, causing people’s frustration and distrust towards the authorities.The authors trace the changes in relations between the power and the people, reveal achievements and, in particular, mistakes of the regional and central government in the given period, which led to adverse consequences.
Keywords: authority; society; Dagestan region; World War I; everyday life.